Meet Samantha : an American girl - Adler, Susan S., 1946-; Niles, Nancy (Madison, Wis. : Pleasant Co., 1986)
In 1904, nine-year-old Samantha, an orphan living with her wealthy grandmother, and her servant friend Nellie have a midnight adventure when they try to find out what has happened to the seamstress who suddenly left her job
610
Accelerated Reader AR
Keywords: Friendship -- Juvenile fiction; Orphans -- Juvenile fiction; Household employees -- Juvenile fiction; Women -- Suffrage -- Juvenile fiction